Self-Metalation of Anchored Porphyrins on Atomically Defined Cobalt Oxide Surfaces: In situ Studies by Surface Vibrational Spectroscopy - Wähler, Tobias; Schuster, Ralf; Libuda, Jörg (Chemistry - A European Journal, 2020)
Metalation of anchored porphyrins is essential for their functionality at hybrid interfaces. In this work, we have studied the anchoring and metalation of a functionalized porphyrin derivative, 5-(4-carboxyphenyl)-10,15,20-triphenylporphyrin (MCTPP), on an atomically-defined CoO(100) film under ultrahigh vacuum (UHV) conditions. We follow both the anchoring to the oxide surface and the self-metalation by surface Co2+ ions via infrared reflection absorption spectroscopy (IRAS). At 150 K, MCTPP multilayer films adsorb molecularly on CoO(100) without anchoring to the surface. Upon heating to 195 K, the first layer of porphyrin molecules anchors via formation of a bridging surface carboxylate. Above 460 K, the MCTPP multilayer desorbs and only the anchored monolayer resides on the surface up to temperatures of 600 K approximately. The orientation of anchored MCTPP depends on the surface coverage. At low coverage, the MCTPP adopts a nearly flat-lying geometry, whereas an upright standing film is formed near the multilayer coverage. Self-metalation of MCTPP depends critically on the surface temperature, the coverage and on the molecular orientation. At 150 K, metalation is largely suppressed, while the degree of metalation increases with increasing temperature and reaches a value of around 60 % in the first monolayer at 450 K. At lower coverage higher metalation fractions (85 % and above) are observed, similar as for increasing temperature.
CRIS-Team Scopus Importer:2020-09-11
Keywords: infrared Spectroscopy; interfaces; metalation; oxide surfaces; porphyrins